2020
DOI: 10.1111/jora.12599
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Disproportionate Minority Contact in the Juvenile Justice System Over the Year Following First Arrest

Abstract: Minority youth are disproportionately represented in the juvenile justice system. Examining how racial disparities relate to biased entry into and continued involvement with the system, while accounting for past and current offending, can provide context about the mechanisms behind overrepresentation. 1,216 adolescents were examined after first arrest to explore associations between race and history of self‐reported offending, likelihood of formal processing, and likelihood of rearrest. Black youth committed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
(86 reference statements)
2
10
0
3
Order By: Relevance
“…Black youth in this study were also more likely than non-Black youth to experience a recidivism arrest in the 5-year follow-up period. This finding aligns with previous literature demonstrating an increased risk of arrest for Black youth, often despite similar rates of self-reported offending across racial/ethnic groups (e.g., Godette et al, 2011;Huizinga et al, 2007;Padgaonkar et al, 2021). Potential reasons for this disparity include an increased likelihood of Black youth living in neighborhoods with concentrated disadvantage and with an increased police presence, as well as implicit biases among legal system actors who may perceive Black youth as more mature and more dangerous than White youth, increasing their risk of arrest for more minor offenses (e.g., Claus et al, 2018;Gase et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Black youth in this study were also more likely than non-Black youth to experience a recidivism arrest in the 5-year follow-up period. This finding aligns with previous literature demonstrating an increased risk of arrest for Black youth, often despite similar rates of self-reported offending across racial/ethnic groups (e.g., Godette et al, 2011;Huizinga et al, 2007;Padgaonkar et al, 2021). Potential reasons for this disparity include an increased likelihood of Black youth living in neighborhoods with concentrated disadvantage and with an increased police presence, as well as implicit biases among legal system actors who may perceive Black youth as more mature and more dangerous than White youth, increasing their risk of arrest for more minor offenses (e.g., Claus et al, 2018;Gase et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Analyses focused on recidivism arrest also revealed that several youth and offense characteristics demonstrated significant relationships with this outcome. In line with previous research (e.g., Cottle et al, 2001; Hoge et al, 1996; Padgaonkar et al, 2021), both gender and race were linked to youths’ likelihood of future arrest. Specifically, female youth were less likely than male youth to incur a recidivism arrest in the 5 years following their referring school-based incident.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, although Black Americans represented 14% of the U.S. population in 2019, they composed 33% of the prison population and 46% of those who had served at least 10 years already (Nellis, 2023). Both perpetration and victimization occur at higher rates in minoritized communities, due in part to racial segregation, disinvestment, and the resulting concentration of poverty; still, crime rates alone do not fully explain racial disparities in the criminal legal system (Padgaonkar et al, 2021; Rosich, 2007). Disparities have been attributed to heightened police patrolling and profiling of Black communities; disproportionate decisions to arrest, detain, and charge Black youth; discriminatory sentencing policies; and more stringent oversight of Black individuals by courts and correctional agencies—often irrespective of the severity of criminal behavior (Padgaonkar et al, 2021; Rosich, 2007; Spinney et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The United States' Juvenile Justice System (JJS) derives much of its structure from the adult criminal justice system and operates in a similarly punitive manner (McCarthy et al, 2016), with confinement serving as both incapacitation and deterrence from crime. Males, racial and ethnic minorities, and youth from socioeconomically disadvantaged households are disproportionately impacted (Spinney et al, 2018;Padgaonkar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%